2017
DOI: 10.1161/jaha.116.005358
|View full text |Cite
|
Sign up to set email alerts
|

Insulin‐Like Growth Factor Binding Protein 4 Fragments Provide Incremental Prognostic Information on Cardiovascular Events in Patients With ST‐Segment Elevation Myocardial Infarction

Abstract: BackgroundFragments of insulin‐like growth factor binding protein 4 (IGFBP‐4) are potential new biomarkers for cardiac risk assessment. The fragments are generated on specific cleavage by pregnancy‐associated plasma protein‐A, which exerts proatherogenic activity. This study investigated the prognostic value of IGFBP‐4 fragments in patients with ST‐segment elevation myocardial infarction.Methods and ResultsWe prospectively included 656 patients with ST‐segment elevation myocardial infarction treated with percu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 41 publications
0
28
1
Order By: Relevance
“…Nonetheless, our results support the evidence that in STEMI patients, IGFBP-4 is associated with an increased risk of adverse events during long term follow-up and favor the hypothesis that its prognostic ability is notable in patients in the acute phase of a myocardial infarction, even in the contemporary setting of routine primary PCI. The prognostic value of intact IGFBP-4 shown in our study, differs from what was previously observed by Postnikov [ 25 ] and Hjortebjerg [ 12 ], where measurements of full-length IGFBP4 were not predictive for MACE and intact IGFBP-4 did not perform better than C reactive protein or peak troponin I for any end point, respectively. These differences may in part be explained by the different immunoassays used in the studies.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Nonetheless, our results support the evidence that in STEMI patients, IGFBP-4 is associated with an increased risk of adverse events during long term follow-up and favor the hypothesis that its prognostic ability is notable in patients in the acute phase of a myocardial infarction, even in the contemporary setting of routine primary PCI. The prognostic value of intact IGFBP-4 shown in our study, differs from what was previously observed by Postnikov [ 25 ] and Hjortebjerg [ 12 ], where measurements of full-length IGFBP4 were not predictive for MACE and intact IGFBP-4 did not perform better than C reactive protein or peak troponin I for any end point, respectively. These differences may in part be explained by the different immunoassays used in the studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Studies of IGFBP-4 as a cardiac risk marker have shown controversial results that may be justified by the differences in the study population, and the clinical setting where the IGFBP-4 was studied. In patients with stable cardiovascular disease, Schulz et al [ 26 ] found that CT- and NT-IGFBP4 levels failed to predict any long-term outcomes, whereas Postnikov et al [ 25 ] found that in patients with symptoms of myocardial ischemia but without ST-segment elevation, both NT- and CT-IGFBP-4 were strong predictors of major adverse cardiac events and more recently, Hjortebjerg et al [ 12 ] found that IGFBP-4 fragments were associated with increased risk of all-cause mortality, cardiovascular mortality and major adverse cardiac events in patients with STEMI. Nonetheless, our results support the evidence that in STEMI patients, IGFBP-4 is associated with an increased risk of adverse events during long term follow-up and favor the hypothesis that its prognostic ability is notable in patients in the acute phase of a myocardial infarction, even in the contemporary setting of routine primary PCI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IGFBP-4, also an abundant IGFBP, has been suggested in numerous studies to be directly involved in the inhibition of atherosclerosis ( 33 , 52 , 54 , 55 , 66 , 67 ). As demonstrated on the level of mRNA and protein, intact IGFBP-4 is produced by a variety of cell types and represents the major IGFBP secreted by myoblasts ( 68 70 ).…”
Section: Igfbp-4 and Papp-amentioning
confidence: 99%
“…The varying results may relate to differences in follow-up period and number of patients and hence, events. Recently, the fragments were shown to prognosticate cardiovascular mortality in 330 type 1 diabetes patients without cardiovascular disease at baseline during 12 years of follow-up ( 54 ) and in 656 patients with STEMI followed for 5 years ( 55 ). Importantly, it was also verified that the IGFBP-4 fragments, unlike PAPP-A, were unaffected by heparin treatment of coronary patients ( 80 ).…”
Section: Igfbp-4 and Papp-amentioning
confidence: 99%